Frequent moving of grazing dairy cows to new paddocks increases the variability of milk fatty acid composition. (8th December 2014) - Coppa, M.; Farruggia, A.; Ravaglia, P.; Pomiès, D.; Borreani, G.; Le Morvan, A.; Ferlay, A.
Abstract : The aim of this work was to investigate the variations of milk fatty acid (FA) composition because of changing paddocks in two different rotational grazing systems. A total of nine Holstein and nine Montbéliarde cows were divided into two equivalent groups according to milk yield, fat and protein contents and calving date, and were allocated to the following two grazing systems: a long duration (LD; 17 days) of paddock utilisation on a heterogeneous pasture and a medium duration (MD) of paddock utilisation (7 to 10 days) on a more intensively managed pasture. The MD cows were supplemented with 4 kg of concentrate/cow per day. Grazing selection was characterised through direct observations and simulated bites, collected at the beginning and at the end of the utilisation of two subsequent MD paddocks, and at the same dates for the LD system. Individual milks were sampled the first 3 days and the last 2 days of grazing on each MD paddock, and simultaneously also for the LD system. Changes in milk FA composition at the beginning of each paddock utilisation were highly affected by the herbage characteristics. Abrupt changes in MD milk FA composition were observed 1 day after the cows were moved to a new paddock. The MD cows grazed by layers from the bottom layers of the previous paddock to the top layers of the subsequent new paddock, resulting in bites with high organic matter digestibility (OMD) value and CP content and a low fibre content at the beginning of each paddock utilisation. These changes could induce significant day-to-day variations of the milk FA composition. The milk fat proportions of 16:0, saturated FA and branched-chain FA decreased, whereas proportions of de novo- synthesised FA, 18:0, c 9-18:1 and 18:2n-6 increased at paddock change. During LD plot utilisation, the heterogeneity of the vegetation allowed the cows to select vegetative patches with higher proportion of leaves, CP content, OMD value and the lowest fibre content. These small changes in CP, NDF and ADF contents of LD herbage and in OMD values, from the beginning to the end of the experiment, could minimally modify the ruminal ecosystem, production of precursors of de novo- synthesised FA and ruminal biohydrogenation, and could induce only small day-to-day variations in the milk FA composition.